Filter material with efficient emulsified water coalescence separation and antibacterial properties as well as preparation method and application of filter material

By preparing organic inorganic composite materials, modifying inorganic particles and coating polyethyleneimine, the porous fiber substrate is imparted with efficient emulsification of water coalescing and separation and antibacterial properties, solving the shortcomings of existing materials in terms of separation efficiency and antibacterial properties, and achieving more efficient and long-lasting filter material performance.

CN119607713AActive Publication Date: 2025-03-14SOUTH CHINA UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411695651.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-14
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing emulsified water coalescing materials have insufficient efficiency in efficient separation of contaminated water in fuel oil. At the same time, due to bacterial growth, the material's antibacterial properties are insufficient, resulting in material failure.

Method used

By preparing organic inorganic composite materials, the surface of inorganic particles is modified with a silane coupling agent, and coated and further modified by polyethyleneimine to form a composite material with self-crosslinking function, imparting high-efficiency emulsification water coalescing and separation and antibacterial properties to the porous fiber substrate.

Benefits of technology

It achieves efficient emulsified water coalescing and separation performance and broad-spectrum antibacterial properties, which can effectively prevent bacterial growth and extend the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119607713A_ABST
    Figure CN119607713A_ABST
Patent Text Reader

Abstract

The invention discloses a filter material with efficient emulsified water coalescence and separation and antibacterial properties as well as a preparation method and application of the filter material. The preparation method comprises the following steps: dispersing inorganic particles with hydroxyl groups on the surfaces in ethanol, adding a silane coupling agent with epoxy groups, and carrying out a heating reaction to prepare an inorganic particle dispersion liquid with epoxy groups on the surfaces; continuing to add polyethyleneimine with a branched chain structure, and reacting to prepare a polyethyleneimine coated and modified inorganic particle dispersion liquid; continuing to add a silane coupling agent with an epoxy group, and reacting to prepare an organic-inorganic composite material dispersion liquid; immersing the porous filter base material into the diluted organic-inorganic composite material dispersion liquid, taking out, drying and curing to obtain the filter material with efficient emulsified water coalescence separation and antibacterial properties. The preparation method is simple, and the prepared filter material has excellent coalescence and separation performance on emulsified water in fuel oil and has a lasting antibacterial effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of filtering and separating materials, and in particular relates to a filter material with high-efficiency emulsified water coalescence separation and antibacterial properties, and a preparation method and application thereof. Background Art

[0002] Contaminated water in fuels such as diesel or aviation kerosene is an important indicator of oil quality and one of the main causes of engine failure. Contaminated water in fuel can decompose certain additives in the oil to form acid, which can corrode the engine injection system and the engine itself; at the same time, the presence of contaminated water will accelerate the oxidation of the oil and generate viscous sludge, which can easily block microporous parts such as nozzles and filters. In addition, under low temperature conditions, the contaminated water in the fuel will freeze and block the engine oil circuit, affecting the fuel supply; the water in the oil will reduce the combustion value of the oil and lead to an increase in the emission of polluting gases. Therefore, it is particularly necessary to separate water from the oil. However, with the development of ultra-low sulfur fuel and biofuel, in order to ensure that the fuel has sufficient lubricity, the content of surfactants added to the oil continues to increase. The added surfactants will be adsorbed on the oil-water interface, resulting in a decrease in the oil-water interfacial tension, a decrease in the particle size of water droplets in diesel, and an increase in stability, which increases the difficulty of water separation.

[0003] At present, the coalescence separation of polluted water in fuel is mainly achieved through coalescence materials. Coalescing separation is to capture water droplets by using interwoven fibers in the filter material. Under the action of fluid, water droplets migrate downstream, and constantly collide and coalesce with water droplets attached to the fibers, causing their size to gradually increase; when the size of water droplets increases to a certain extent, collisions between water droplets can also occur, and coalescence is further increased. Finally, under the action of gravity and fluid drag, the droplets detach from the outflow surface of the material and self-sediment and separate. The coalescence separation method has high separation efficiency, low energy consumption, and large processing flow. It can meet the complexity of the oil-water system required to be filtered in the actual working conditions of fuel. Therefore, it is a commonly used method at present, but the coalescence separation efficiency needs to be further improved. At the same time, the process of coalescence material to achieve demulsification and coalescence of emulsified water will cause the coalescence material to maintain a high water content inside, so it is easy for bacteria to grow and multiply rapidly on the surface of the coalescence material. The growth of bacteria on the surface of the material will adhere to the surface of the material or destroy the surface of the material, which may cause the failure of the coalescence material. Therefore, in addition to good coalescence performance, if the surface of the coalescence material also has good antibacterial properties, the negative impact of bacterial growth can be avoided. However, the current emulsified water coalescence materials rarely have both efficient coalescence and separation performance and excellent and long-lasting antibacterial properties. Summary of the invention

[0004] In order to overcome the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a filter material with high-efficiency emulsified water coalescence separation and antibacterial properties, and its preparation method and application; the filter material obtained by the present invention not only has high-efficiency water coalescence separation performance, but also has excellent antibacterial properties; and the preparation method is simple and can be used for different porous fiber substrates.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a filter material with high-efficiency emulsified water coalescence separation and antibacterial properties, comprising the following steps:

[0007] Step 1, dispersing inorganic particles with hydroxyl groups on the surface in 20-30 times the mass of ethanol, adding a silane coupling agent with epoxy groups, heating to 60-70° C. for reaction for 3-5 hours, and preparing a dispersion of inorganic particles with epoxy groups on the surface; the average particle size of the inorganic particles is 0.3-3.0 μm;

[0008] Step 2, continue to add branched polyethyleneimine, react at 60-70° C. for 2-4 hours to prepare a polyethyleneimine-coated modified inorganic particle dispersion; the molecular weight of the polyethyleneimine is 1800-10000; the mass of the polyethyleneimine is 200-400% of the inorganic particles;

[0009] Step 3, continue to add a silane coupling agent with an epoxy group, react at 70-75° C. for 2-4 hours, and prepare an organic-inorganic composite material dispersion; the mass of the silane coupling agent is 25-45% of the inorganic particles;

[0010] Step 4, immersing the porous filter substrate in the diluted organic-inorganic composite material dispersion for 10 to 60 minutes, taking it out, drying it, and curing it to obtain a filter material with high-efficiency emulsified water agglomeration separation and antibacterial properties.

[0011] Preferably, in step 1, the inorganic particles are at least one of silicon dioxide and titanium dioxide;

[0012] Preferably, in step 1, the average particle size of the inorganic particles is 0.5-2.0 μm.

[0013] Preferably, in step 1, the silane coupling agent is at least one of 3-glycidyloxypropyltrimethoxysilane, 3-(2,2-epoxypropylene)propyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltriethoxysilane;

[0014] Preferably, in step 1, the mass of the silane coupling agent is 10-30wt% of the inorganic particles.

[0015] Further preferably, in step 1, the mass of the silane coupling agent is 15-25wt% of the inorganic particles.

[0016] Preferably, in step 2, the molecular weight of the polyethyleneimine is 3000-7000;

[0017] Preferably, in step 2, the mass of the polyethyleneimine is 200-350% of the inorganic particles.

[0018] Preferably, in step 3, the silane coupling agent is at least one of 3-glycidyloxypropyltrimethoxysilane, 3-(2,2-epoxypropylene)propyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltriethoxysilane;

[0019] Preferably, in step 3, the mass of the silane coupling agent is 30-40% of the inorganic particles.

[0020] Preferably, in step 4, the porous filter substrate is a porous fiber substrate.

[0021] Preferably, in step 4, the porous filter substrate is one of filter paper and non-woven fabric.

[0022] Preferably, in step 4, the mass concentration of the diluted organic-inorganic composite material dispersion is 2-8%.

[0023] Further preferably, the mass concentration of the diluted organic-inorganic composite material dispersion is 3-5%.

[0024] Preferably, in step 4, the drying temperature is 50-100°C and the time is 20-60min;

[0025] Further preferably, the drying temperature is 50-80°C and the drying time is 30-60min;

[0026] Preferably, in step 4, the curing temperature is 120-150° C. and the curing time is 10-30 min.

[0027] More preferably, the curing temperature is 120-130° C. and the curing time is 20-40 min.

[0028] The filter material prepared by the above preparation method has high-efficiency emulsified water coalescence separation and antibacterial properties.

[0029] Preferably, the filter material with high-efficiency emulsified water coalescence separation and antibacterial properties includes a porous filter substrate and an organic-inorganic composite material, the organic-inorganic composite material is loaded on the porous filter substrate, and the mass ratio of the porous filter substrate to the organic-inorganic composite material is 95:5-85:15.

[0030] Further preferably, the mass ratio of the porous filter substrate to the organic-inorganic composite material is 95:5-90:10.

[0031] The above-mentioned filter material with high efficiency emulsified water coalescence separation and antibacterial properties is used in oil-water separation.

[0032] Preferably, the oil and water separated from the oil and water contains a surfactant, that is, an oil liquid containing emulsified water.

[0033] The present invention firstly uses a silane coupling agent to modify the surface of inorganic particles to introduce epoxy groups, then further grafts and modifies them through polyethyleneimine to form organic polyethyleneimine-coated inorganic particles, and finally further modifies the surface of organic-coated inorganic particles through a silane coupling agent to introduce siloxane groups with self-crosslinking function, thereby preparing the target organic-inorganic composite material. The porous fiber substrate is immersed in the organic-inorganic composite material diluted to a suitable concentration, taken out, dried, and solidified, and a filter material with high-efficiency emulsified water coalescence separation and antibacterial performance (coalescing separation filter material obtained after the organic-inorganic composite material is treated) can be prepared.

[0034] The preparation mechanism of the organic-inorganic composite material of the present invention is as follows:

[0035]

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The present invention prepares the organic-inorganic composite material, and can endow various porous fiber substrates with excellent emulsified water aggregation and separation performance and antibacterial performance through a simple impregnation and drying solidification method. The polyethyleneimine in the organic-inorganic composite material has good hydrophilic and lipophilic properties, which can give the material surface excellent emulsified water aggregation properties, and at the same time provide the material with efficient and broad-spectrum antibacterial properties, and can inactivate and inhibit a variety of bacteria including Escherichia coli and Staphylococcus aureus; in addition, due to the presence of siloxane groups with self-crosslinking function in the organic-inorganic composite material, a polymer network structure can be formed during the curing process, thereby improving the adhesion performance and oil resistance of the organic-inorganic composite material on the filter material fiber; and the inorganic particle components in the organic-inorganic composite material can be permanently and firmly attached to the surface of the porous substrate and form a protruding structure through chemical bonding and fixation with the organic polymer phase, which can make the protruding structure on the surface of the material increase the probability of capturing water droplets when the emulsified water passes through the interior of the porous substrate, thereby further improving the aggregation and separation performance of the material; in addition, the protruding structure on the surface of the filter material fiber and the polyethyleneimine structure with antibacterial properties can further enhance the antibacterial properties of the filter material. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a schematic diagram of the oil-water separation test bench of the present invention.

[0039] Figure 2 This is a SEM image of the glass fiber substrate of the agglomerated material of the present invention.

[0040] Figure 3 This is a SEM image of the agglomerated material after the organic-inorganic composite material is treated in Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0042] The experimental methods described in the examples of the present invention are conventional methods unless otherwise specified; the raw materials and reagents used in the examples are commercially available unless otherwise specified.

[0043] The glass fiber substrate of the following examples is prepared by the following method: the base paper weight is controlled at 80 g / m 2 , weigh glass wool fiber 19°SR (purchased from Yulin Tianshengyuan Glass Fiber Technology Co., Ltd.) and glass fiber (purchased from Shenzhen Xinxian Technology Co., Ltd.) at a mass ratio of 4:6, add dilute sulfuric acid, and make the pH value of the mixed solution in the container between 2-3. Then, transfer the fiber to the deflaker for deflaking. After the fiber is dispersed, transfer the deflaked slurry to the automatic sheet making machine. Finally, filter the water, peel off the paper, and place the wet paper web on a flat dryer at 105°C to dry to constant weight.

[0044] Example 1

[0045] The filter material with high-efficiency emulsified water coalescence separation and antibacterial performance and the preparation method thereof are prepared according to the following steps according to the following formula:

[0046] Step 1: Disperse 10 g of silica powder (average particle size 1.2 μm) into 240 g of ethanol, add 2.0 g of silane coupling agent 3-glycidyloxypropyltrimethoxysilane, and heat to 65° C. for 3 h;

[0047] Step 2: Add 30 g of branched polyethyleneimine (molecular weight 3000), heat to 70° C. and react for 2 h to prepare a polyethyleneimine-coated modified inorganic particle dispersion;

[0048] Step 3: Continue to add 3.5 g of silane coupling agent 3-glycidyloxypropyltrimethoxysilane, raise the temperature to 75° C. and react for 2 hours to prepare an organic-inorganic composite material dispersion;

[0049] Step 4: Immerse the circular filter glass fiber substrate with a diameter of 20 cm obtained by papermaking into 200 mL of the organic-inorganic composite material dispersion prepared in step 3 (diluted to 3.0 wt% by ethanol solvent) for 30 minutes; take out and dry at 60°C for 60 minutes, and then cure at 120°C for 15 minutes to obtain a filter material with high-efficiency emulsified water agglomeration separation and antibacterial properties.

[0050] Example 2

[0051] The filter material with high-efficiency emulsified water coalescence separation and antibacterial performance and the preparation method thereof are prepared according to the following steps according to the following formula:

[0052] Step 1: Disperse 15 g of titanium dioxide powder (average particle size of about 2.3 μm) in 300 g of ethanol, add 2.5 g of silane coupling agent β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and heat to 62 ° C for 4 h;

[0053] Step 2: Add 45 g of branched polyethyleneimine (molecular weight 7000), heat to 68° C. and react for 2.5 h to prepare a polyethyleneimine-coated modified inorganic particle dispersion;

[0054] Step 3: Continue to add 5.0 g of silane coupling agent β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, raise the temperature to 75° C. and react for 2 hours to prepare an organic-inorganic composite material dispersion;

[0055] Step 4: Immerse the circular filter glass fiber substrate with a diameter of 20 cm obtained by papermaking into 200 mL of the organic-inorganic composite material dispersion prepared in step 3 (diluted to 3.0 wt% by ethanol solvent) for 30 minutes; take out and dry at 60°C for 30 minutes, and then cure at 120°C for 15 minutes to obtain a filter material with high-efficiency emulsified water agglomeration separation and antibacterial properties.

[0056] Example 3

[0057] The filter material with high-efficiency emulsified water coalescence separation and antibacterial performance and the preparation method thereof are prepared according to the following steps according to the following formula:

[0058] Step 1: Disperse 10 g of silica powder (average particle size of about 0.8 μm) into 250 g of ethanol, add 2.8 g of silane coupling agent β-(3,4-epoxycyclohexyl)ethyltriethoxysilane, and heat to 64 ° C for 4 h;

[0059] Step 2: Add 32 g of branched polyethyleneimine (molecular weight 7000), heat to 70° C. and react for 2 h to prepare a polyethyleneimine-coated modified inorganic particle dispersion;

[0060] Step 3: Continue to add 4.3 g of silane coupling agent β-(3,4-epoxycyclohexyl)ethyltriethoxysilane, raise the temperature to 75° C. and react for 2 hours to prepare an organic-inorganic composite material dispersion;

[0061] Step 4: Immerse the circular filter glass fiber substrate with a diameter of 20 cm obtained by papermaking into 200 mL of the organic-inorganic composite material dispersion prepared in step 3 (diluted to 3.0 wt% by ethanol solvent) for 15 minutes; take out and dry at 60°C for 40 minutes, and then cure at 120°C for 15 minutes to obtain a filter material with high-efficiency emulsified water agglomeration separation and antibacterial properties.

[0062] Comparative Example 1

[0063] The process formula of Comparative Example 1 is basically the same as that of Example 1, except that the amount of silicon dioxide in step 1 is reduced from 10 g to 2.5 g.

[0064] Comparative Example 2

[0065] The process formula of Comparative Example 2 is basically the same as that of Example 2, except that the amount of titanium dioxide in step 1 is adjusted from 10 g to 25.0 g.

[0066] Comparative Example 3

[0067] The process formula of comparative example 3 is basically the same as that of example 1, except that the molecular weight of polyethyleneimine in step 2 is increased to 70000. The product prepared in step 3 has high viscosity and forms gel in the late stage of the reaction in step 4, which is unusable.

[0068] Comparative Example 4

[0069] The process formula of Comparative Example 4 is basically the same as that of Example 1, except that the molecular weight of polyethyleneimine in step 2 is only 1000.

[0070] Comparative Example 5

[0071] The process formula of Comparative Example 5 is basically the same as that of Example 1, except that the amount of silane coupling agent in step 3 is 1.0 g.

[0072] Comparative Example 6

[0073] The process formula of comparative example 6 is basically the same as that of example 1, except that the amount of silane coupling agent in step 3 is too high by 6.0 g. The product prepared by the system in step 3 has high viscosity, and gel is formed in the late stage of the reaction in step 4, which is unusable.

[0074] Comparative Example 7

[0075] The process formula of Comparative Example 7 is basically the same as that of Example 1, except that the average particle size of the silicon dioxide in step 1 is 100 nm.

[0076] Comparative Example 8

[0077] The silica particles are dispersed in ethanol, and no organic components are added for reaction, and the glass fiber substrate is directly soaked. The details are as follows:

[0078] Step 1: Disperse 10 g of silicon dioxide powder (average particle size of 1.2 μm) into 240 g of ethanol to prepare an inorganic material dispersion;

[0079] Step 2: Immerse the circular filter glass fiber substrate with a diameter of 20 cm obtained by papermaking into 200 mL of the inorganic material dispersion prepared in step 1 (diluted to 3.0 wt% by ethanol solvent) for 30 minutes; take out and dry at 60°C for 60 minutes, and then cure at 120°C for 15 minutes to obtain the filter material.

[0080] Comparative Example 9

[0081] The process formula of comparative example 9 is basically the same as that of example 1, except that step 1 and step 2 are reduced, that is, only the organic component of silane coupling agent-modified polyethyleneimine is generated for soaking the glass fiber substrate. The details are as follows:

[0082] Step 1: Disperse 30 g of branched polyethyleneimine (molecular weight 3000) into 240 g of ethanol, add 3.5 g of silane coupling agent 3-glycidyloxypropyltrimethoxysilane, heat to 75° C. and react for 2 h to prepare an organic material dispersion;

[0083] Step 2: Immerse the circular filter glass fiber substrate with a diameter of 20 cm obtained by papermaking into 200 mL of the organic material dispersion prepared in step 1 (diluted to 3.0 wt% by ethanol solvent) for 30 minutes; take out and dry at 60°C for 60 minutes, and then cure at 120°C for 15 minutes to obtain the filter material.

[0084] Comparative Example 10

[0085] The silicon dioxide particles of Comparative Example 8 and the silane coupling agent-modified polyethyleneimine of Comparative Example 9 are directly blended. The details are as follows:

[0086] Step 1: Disperse 10 g of silicon dioxide powder (average particle size of 1.2 μm) into 240 g of ethanol to prepare an inorganic material dispersion;

[0087] Step 2: Disperse 30 g of branched polyethyleneimine (molecular weight 3000) into 240 g of ethanol, add 3.5 g of silane coupling agent 3-glycidyloxypropyltrimethoxysilane, heat to 75° C. and react for 2 h to prepare an organic material dispersion;

[0088] Step 3: mixing the inorganic material dispersion of step 1 and the organic material dispersion of step 2 to obtain a blended dispersion of the inorganic material and the organic material;

[0089] Step 4: Immerse the circular filter glass fiber substrate with a diameter of 20 cm obtained by papermaking into 200 mL of the mixed dispersion of the inorganic material and organic material in step 3 (diluted to 3.0 wt% by ethanol solvent) for 30 minutes; take out and dry at 60°C for 60 minutes, and then cure at 120°C for 15 minutes to obtain the filter material.

[0090] The water separation performance and antibacterial performance of the filter materials with high efficiency emulsified water coalescence separation and antibacterial performance of Examples 1-3 and Comparative Examples 1, 2, 4, 5, 7, 9, and 10 were tested by the water separation test method and antibacterial performance test method described below.

[0091] Antibacterial performance test: The antibacterial performance of the filter material was tested according to the standard method of GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method". 5 mL of bacterial solution with a concentration of 1×10 8 cfu / mL-5×10 8 cfu / mL of experimental bacterial solution was placed in a conical flask filled with 70mL of 0.03mol / L PBS buffer (2.84g disodium hydrogen phosphate, 1.36g potassium dihydrogen phosphate, 1000mL water), and 0.75g of the shredded filter material was added. The conical flask was placed on a constant temperature water bath shaker and cultured at (24±1)℃ at 150rpm for different times. After the specified time, the experimental mixture was diluted to an appropriate multiple with 0.03mol / L PBS buffer, transferred to nutrient agar medium, and cultured at (37±1)℃ for 24h-48h before counting and calculating the antibacterial rate. The test strains include Staphylococcus aureus (S.aureus) and Escherichia coli (E.coli).

[0092] Water separation test method: Use the oil-water separation test bench (such as Figure 1The water separation performance of the filter material was tested as shown in Figure 1. First, different types of surfactants were dissolved in a measured mixture of diesel and tap water (the oil-water mass ratio was 90:10, and the oil was No. 0 diesel). In this experiment, nonionic surfactant nonylphenol polyoxyethylene ether (NP-10) was selected, and the addition amount was 0.1wt% of the oil-water mixture. The oil-water mixture was emulsified at 5000rpm by a high-speed disperser for 30 minutes to obtain an oil-water emulsion. After the filter material sample was placed in the fixture, the emulsion was pumped through the filter material sample at a set flow rate. The samples taken out from the upstream and downstream liquid ports were tested for water content using a Karl Fischer titrator (C20 type, METTLER TOLEDO, Switzerland). The samples were sampled and measured every 15 minutes. When the experimental time reached 1 hour, the test was terminated. The average value of several sampling tests was the total water content of the upstream and downstream. According to the calculation formula: water separation efficiency (%) = upstream water content - downstream water content) / upstream water content * 100%, the calculation result is the water separation efficiency. After the filter material sample test is completed, continue to immerse it in the tested oil-water mixture. After leaving it at room temperature for one month, continue to test the water separation efficiency again. Record it as the water separation performance after one month, and observe whether there is bacterial plaque on the surface of the filter material.

[0093] The water separation and antibacterial performance test results of the filter materials of the embodiment and the comparative example are shown in Table 1 below:

[0094] Table 1 Performance test results of each embodiment and comparative example

[0095]

[0096] It can be seen from the water separation test data in Table 1 that the filter materials prepared by Examples 1-3 of the present invention have good coalescence separation performance for emulsified water in oil, and the materials can still maintain high water separation performance after being immersed in the oil-water mixture for one month. In addition, the filter materials have good antibacterial properties, and the antibacterial efficiency against golden Gluconobacter and Escherichia coli is more than 99%, and no bacterial plaque is found after being immersed in the oil-water mixture for one month.

[0097] Compared with the untreated glass fiber substrate ( Figure 2 ), the filter material after the treatment of the organic-inorganic composite material in Example 1 ( Figure 3 ) fibers are covered with inorganic particles, which can further enhance the capture and aggregation of emulsified water droplets on the filter material fibers, thus achieving excellent aggregation effects.

[0098] Since Comparative Example 1 does not introduce enough inorganic particles, there are not many protruding structures on the surface of the filter material fiber, so the agglomeration separation performance is much lower than that of Example 1. In addition, the antibacterial performance of the filter material in Comparative Example 1 is also significantly lower than that of Example 1, which further illustrates that the nanoparticles on the surface of the filter material can greatly improve the antibacterial performance of the filter material in addition to improving the water separation performance of the filter material.

[0099] In Comparative Example 2, the proportion of inorganic particle components is too high, resulting in the failure of the organic phase component to fully modify the surface of the inorganic particles and to stably bond and fix them. As a result, part of the organic-inorganic composite material was swollen and fell off by the oil during the test and long-term immersion process, resulting in a significant decrease in the agglomeration performance and the antibacterial performance of the filter material.

[0100] In Comparative Example 3, since the molecular weight of the polyethyleneimine used was too large, the product during the reaction had a high viscosity and formed a gel in the later stage of the reaction, and could not be used.

[0101] In Comparative Example 4, since the molecular weight of polyethyleneimine used was too small, the reinforced glass fiber filter material was brittle and had low strength. The filter material broke during the water separation test, so the full process test of water separation performance could not be performed.

[0102] In Comparative Example 5, since the amount of silane coupling agent added in step 3 is too low, the crosslinking density of the organic-inorganic composite system is low. In the water separation performance and antibacterial performance tests, the resin is dissolved, and the agglomeration separation performance and antibacterial performance are low. During the long-term immersion in the oil-water mixture, the resin is dissolved, the filter material has a loose structure, and the strength is significantly reduced, and it cannot meet the water separation performance test requirements. In addition, the resin is dissolved, which also causes the filter material to lose its antibacterial properties, resulting in the appearance of bacterial plaque.

[0103] In Comparative Example 6, since the amount of silane coupling agent added in step 3 is too high, the product during the reaction has high viscosity and forms a gel in the later stage of the reaction, which cannot be used.

[0104] In Comparative Example 7, since the size of the inorganic particles is too small, they are completely covered by the organic phase, and the protrusions on the surface of the filter material fiber are not obvious. Therefore, the agglomeration separation performance and antibacterial performance are much lower than those in Example 1.

[0105] Since Comparative Example 8 only has inorganic particles, the binding force between the inorganic particles and the glass fiber substrate fibers cannot enhance the filter material. Therefore, when immersed in the oil-water mixture for water separation test, the filter material fibers fall off and the entire filter material structure falls apart, making it impossible to test or apply.

[0106] Since the product of Comparative Example 9 is only polyethyleneimine modified by a silane coupling agent, after being applied to a glass fiber filter material, its agglomeration separation performance and antibacterial performance are low; at the same time, since it is not an organic-inorganic composite system, its oil resistance is reduced, and part of the resin is dissolved after long-term immersion in an oil-water mixture, resulting in a significant decrease in the water separation performance of the filter material after one month, and its antibacterial performance is also reduced, resulting in the appearance of bacterial plaque.

[0107] In Comparative Example 10, due to the direct blending of inorganic particles and organic components, phase separation occurred between the inorganic components and the organic components during the application process, and the inorganic components agglomerated, failing to form uniform protrusions on the surface of the glass fiber filter material, resulting in low agglomeration separation performance and antibacterial performance. In addition, the organic components and the inorganic components did not form a good chemical bond coating combination, and their oil resistance was poor. After long-term immersion in an oil-water mixture, part of the resin was dissolved, resulting in a significant decrease in the water separation performance of the filter material after one month, and the antibacterial performance also decreased, resulting in the appearance of plaque.

Claims

1. A method for preparing a filter material with high-efficiency emulsified water coalescence separation and antibacterial properties, characterized in that: The following steps are involved: Step 1, dispersing inorganic particles with hydroxyl groups on the surface in 20-30 times the mass of ethanol, adding a silane coupling agent with epoxy groups, heating to 60-70° C. for reaction for 3-5 hours, and preparing a dispersion of inorganic particles with epoxy groups on the surface; the average particle size of the inorganic particles is 0.3-3.0 μm; Step 2, continue to add branched polyethyleneimine, react at 60-70° C. for 2-4 hours to prepare a polyethyleneimine-coated modified inorganic particle dispersion; the molecular weight of the polyethyleneimine is 1800-10000; the mass of the polyethyleneimine is 200-400% of the inorganic particles; Step 3, continue to add a silane coupling agent with an epoxy group, react at 70-75° C. for 2-4 hours, and prepare an organic-inorganic composite material dispersion; the mass of the silane coupling agent is 25-45% of the inorganic particles; Step 4, immersing the porous filter substrate in the diluted organic-inorganic composite material dispersion for 10 to 60 minutes, taking it out, drying it, and curing it to obtain a filter material with high-efficiency emulsified water agglomeration separation and antibacterial properties.

2. The method for preparing a filter material with high-efficiency emulsified water coalescence separation and antibacterial properties according to claim 1, characterized in that: In step 1, the inorganic particles are at least one of silicon dioxide and titanium dioxide; In step 1, the average particle size of the inorganic particles is 0.5-2.0 μm.

3. The method for preparing a filter material with high-efficiency emulsified water coalescence separation and antibacterial properties according to claim 1, characterized in that: In step 1, the silane coupling agent is at least one of 3-glycidyloxypropyltrimethoxysilane, 3-(2,2-epoxypropylene)propyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltriethoxysilane; In step 1, the mass of the silane coupling agent is 10-30wt% of the inorganic particles.

4. The method for preparing a filter material with high-efficiency emulsified water coalescence separation and antibacterial properties according to claim 3, characterized in that: In step 1, the mass of the silane coupling agent is 15-25wt% of the inorganic particles.

5. The method for preparing a filter material with high-efficiency emulsified water coalescence separation and antibacterial properties according to claim 1, characterized in that: In step 2, the molecular weight of the polyethyleneimine is 3000-7000; In step 2, the mass of the polyethyleneimine is 200-350% of the inorganic particles.

6. The method for preparing a filter material with high-efficiency emulsified water coalescence separation and antibacterial properties according to claim 1, characterized in that: In step 3, the silane coupling agent is at least one of 3-glycidyloxypropyltrimethoxysilane, 3-(2,2-epoxypropylene)propyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltriethoxysilane; In step 3, the mass of the silane coupling agent is 30-40% of the inorganic particles.

7. The method for preparing a filter material with high-efficiency emulsified water coalescence separation and antibacterial properties according to claim 1, characterized in that: In step 4, the porous filter substrate is one of filter paper and non-woven fabric; In step 4, the mass concentration of the diluted organic-inorganic composite material dispersion is 2-8%; In step 4, the drying temperature is 50-100°C and the time is 20-60min; In step 4, the curing temperature is 120-150° C. and the curing time is 10-30 minutes.

8. A filter material having high-efficiency emulsified water coalescence separation and antibacterial properties prepared by the preparation method according to any one of claims 1 to 7.

9. The filter material with high efficiency emulsified water coalescence separation and antibacterial performance according to claim 8, characterized in that: The filter material with high-efficiency emulsified water coalescence separation and antibacterial performance includes a porous filter substrate and an organic-inorganic composite material. The organic-inorganic composite material is loaded on the porous filter substrate, and the mass ratio of the porous filter substrate to the organic-inorganic composite material is 95:5-85:

15.

10. Use of the filter material with high-efficiency emulsified water coalescence separation and antibacterial properties as claimed in any one of claims 8 to 9 in oil-water separation.

Citation Information

Patent Citations

  • Glass fiber ball bundle loaded MXene / TiO2 aerogel composite material and preparation method thereof

    CN114377706A

  • Compound natural plant extract synergistic antibacterial and antiviral multi-shell microcapsule as well as preparation method and application thereof

    CN115104605A

  • Oil-water separation coalescence fiber material as well as preparation method and application thereof

    CN115430177A

  • Submerged double-lyophobic oil-water separation membrane as well as preparation method and application thereof

    CN115487687A

  • Polymer with efficient and long-acting demulsification and coalescence functions for emulsified water as well as preparation method and application of polymer

    CN119080993A